2021
DOI: 10.3390/foods10091987
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residue Behavior and Risk Assessment in Celery after Se Nanoparticles Application

Abstract: This study investigates pesticide levels in celery, and compares their degradation, dissipation, distribution, and dietary risk after spraying with selenium (Se) nanoparticles. Abamectin, imidacloprid, acetamiprid, thiamethoxam, and lambda-cyhalothrin were sprayed at 1.6, 6.8, 2.0, 1.0, and 0.7 g a.i. ha−1 followed by a 2 g·ha−1 Se nanoparticle application during the growing period. Thiamethoxam, abamectin, imidacloprid, lambda-cyhalothrin, and acetamiprid in celery degraded following a first order kinetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An additional investigation found that the application of sodium selenite (Na 2 SeO 4 ) as a soil amendment resulted in increased levels of secondary metabolites (including total phenols, flavonoids, and anthocyanins) in Brassica juncea L. plants that were exposed to Cr . Kang et al showed that nano-Se application accelerated the decomposition of thiamethoxam, abamectin, imidacloprid, and λ-cyhalothrin in celery . Applying nano-Se (10 mg/L) via foliar reinforcement in tea plants has improved the adverse effects of pesticide stress caused by imidacloprid, acetamiprid, and difenoconazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional investigation found that the application of sodium selenite (Na 2 SeO 4 ) as a soil amendment resulted in increased levels of secondary metabolites (including total phenols, flavonoids, and anthocyanins) in Brassica juncea L. plants that were exposed to Cr . Kang et al showed that nano-Se application accelerated the decomposition of thiamethoxam, abamectin, imidacloprid, and λ-cyhalothrin in celery . Applying nano-Se (10 mg/L) via foliar reinforcement in tea plants has improved the adverse effects of pesticide stress caused by imidacloprid, acetamiprid, and difenoconazole.…”
Section: Discussionmentioning
confidence: 99%
“…38 Kang et al showed that nano-Se application accelerated the decomposition of thiamethoxam, abamectin, imidacloprid, and λ-cyhalothrin in celery. 39 Applying nano-Se (10 mg/L) via foliar reinforcement in tea plants has improved the adverse effects of pesticide stress caused by imidacloprid, acetamiprid, and difenoconazole. This improvement is achieved through the modulation and regulation of the antioxidant system, nutritional levels (specifically tea polyphenols and catechins), and secondary metabolism (total phenols and flavonoids).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Abamectin was detected during field trials, and if fresh pods are consumed after harvest, the presence of these pesticides in food is anticipated to have a negative impact on human health. Several studies have assessed the risk of abamectin on various crops, including strawberries (Song et al, 2020), mangoes (Bian et al, 2020), okra (Ratnamma et al, 2020), celery (Kang et al, 2021), and wolfberry plants (Jing et al, 2021). However, there is currently no information in the literature regarding the risk assessment of abamectin application on fresh corn, bitter melon, and Fritillaria .…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnologies are being actively introduced into various spheres of human economic activity [18][19][20][21][22]. In particular, there are encouraging developments in the field of agrochemistry [23][24][25][26][27][28]. Innovative nanopesticides are nanomaterials developed for plant protection and characterized by the following properties: minimizing losses during the application, increasing leaf coverage, increasing stability, and reducing the amount of consumption of active substances.…”
Section: Introductionmentioning
confidence: 99%